Indestructible micro identification of histamine in fish samples using ATR-FTIR spectroscopy - Faras Zahra, Fajriyaningsih; Muhammad Abdurrahman, Munir; Fitria, Rahmawati; Adhi, Gunawan (AIP Publishing, 2025)
The decarboxylation of histidine can form histamine. It is a heterocyclic amine that is very poisonous if consumed more than 50 ppm per day. The histamine investigation in food is imperative owing to the poisons of histamine. This paper describes the approach of histamine analysis using FTIR. The application of FTIR is simple, easy, and fast. Furthermore, histamine does not require the derivatization step of the chromatography method. Furthermore, attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy was applied as a non-destructive technique (Mid, 4000 – 650 cm−1) to identify histamine in fish samples. Regarding validation, the Commission Decision 657/2002/CE was applied. The validation of selectivity, accuracy, precision, detection limit, and quantitation limit outcomes revealed that the technique was satisfactory. The linear range between 10−3 – 10−1 nmol‧L−1 was applied. The histamine investigation using ATR-FTIR showed the superiority of this technique compared to LC/MS and GC/MS and can be applied for histamine detection in actual samples.